The Life and Theology of Alexander Knox (1757-1831) : Anglicanism in the Age of Enlightenment and Romanticism - McCready, David, (Anglican-Episcopal Theology and History;, 2020)
In his The Life and Theology of Alexander Knox, David McCready highlights one of the most important figures in the history of Anglicanism. A disciple of John Wesley, Knox presents his mentor as a representative of the Neo-Platonic tradition within Anglicanism, a tradition that Knox himself also exemplifies. Knox also significantly impacted John Henry Newman and the Tractarians. But Alexander Knox is an important theologian in his own right, one who engaged substantially with the main intellectual currents of his day, namely those stemming from the Enlightenment and Romanticism. Meshing Knox's theological teaching on various topics with details of his life, this book offers a fascinating portrait of a man who, in the words of Samuel Taylor Coleridge 'changed the minds, and, with them, the acts of thousands.'.